Comissões de Integração Ensino-Serviço: (des)montando os quebra-cabeças da Educação Permanente (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2019)
Teaching-Service Integration Committees: (dis)assembling the Permanent Education jigsaw puzzle